Researsch of the system of protection of the medieval city of Syganak (Journal of history-rus, 2021)
The article, based on medieval historical sources and research conducted on the medieval city of Sygnak, provides a brief overview of the role and significance of the city in the history of the Kazakh na- tion. One of the major centers on the Great Silk Road, the most important city on the Syr Darya, Sygnak has long been a well-developed culture, economy, crafts and trade, agriculture and cattle breeding. In the XI–XIII centuries it was known as one of the centers of the Kypchak Khanate, in the XIV–XV centu- ries it was the capital of Ak Orda, and in the XV–XVI centuries it was the capital of the Kazakh Khanate, becoming the political and economic center of the khanate. The defensive system of the medieval city of Sygnak, including the fortified walls with gates, has not been sufficiently studied, therefore, within the framework of this topic, we decided to conduct research work, identify the specifics of the city’s defen- sive system and introduce it into scientific circulation. The article examines the results of archaeological research carried out at the medieval settlement of Syganak, analyzes the architectural features of the eastern gates and fortress walls of the city, manufacturing technology and building materials. In addition, a comparative analysis of the Signak gate with the gates of medieval cities in the region was carried out and additional scientific conclusions were drawn. Based on field data obtained during the excavations, the chronology of the eastern gate and fortress walls was determined.Key words: Syganak, protection system, gate, Syrdarya, middle ages, medieval cities.